2015
DOI: 10.4236/ojped.2015.53033
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome during Pediatric Residency Training

Abstract: Background: Burnout syndrome is a common professional problem causing mental fatigue, depersonalization, and diminished self-value. Burnout during pediatric residency can significantly influence the resident's performance and the quality of their training. Objectives: To evaluate the burnout status of pediatric residents across Jeddah, KSA. Methods: A cross-sectional, descriptive study involving pediatric residents across Jeddah, Saudi Arabia was conducted from the 1 st of August to 1 st of December, 2012. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…17,18 Junior residents commonly had burnout more compared to senior residents due to increased work load, lack of experiences and responsibilities. 2 Learning environment can minimize the risk of burnout on residents by reduce unnecessary workload and schedule time arrangements. 19 The high response rate and multicentre sites, which involved all pediatric training institutions in Indonesia is the strength of our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Junior residents commonly had burnout more compared to senior residents due to increased work load, lack of experiences and responsibilities. 2 Learning environment can minimize the risk of burnout on residents by reduce unnecessary workload and schedule time arrangements. 19 The high response rate and multicentre sites, which involved all pediatric training institutions in Indonesia is the strength of our study.…”
Section: Resultsmentioning
confidence: 99%
“…The high workload and complex learning environment during pediatric training program may cause exhaustion and disengagement of the trainees. 1,2 This can result in burnout, which manifest as a syndrome of emotional exhaustion, depersonalization and a reduced of personal accomplishment. It has been reported that burnout among medical residents/trainees was very common, not only in surgical/urgency trainees but also in other specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is known worldwide as a work-related syndrome, which is a triad of emotional exhaustion, depersonalization, and lack of personal accomplishment. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…They often feel unsatisfied with their work and accomplishments, which eventually affects the quality of patient care. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%